Payroll : a guide to running an efficient department - Lambert, Vicki (Wiley, 2005)
This book will help anyone who is responsible for a payroll department to manage payroll functions with the maximum efficiency and within compliance requirements. It will demonstrate the optimal methods for the basic functions of payroll through to year end and management.